Pre‐existing diabetes is a risk factor for increased rates of cellular rejection after kidney transplantation: an observational cohort study. Issue 8 (5th June 2017) - Johal, S.; Jackson‐Spence, F.; Gillott, H.; Tahir, S.; Mytton, J.; Evison, F.; Stephenson, B.; Nath, J.; Sharif, A.
Abstract: Aim: To investigate whether people with diabetes have an elevated risk of kidney allograft rejection in a well characterized clinical cohort in the setting of contemporary immunosuppression. Methods: We conducted a retrospective cohort study including all kidney allograft recipients at a single centre between 2007 and 2015, linking clinical, biochemical and histopathological data from electronic patient records. Results: Data were analysed for 1140 kidney transplant recipients. The median follow‐up was 4.4 years post‐transplantation, and 117 of the kidney transplant recipients (10.2%) had diabetes at time of transplantation. Kidney allograft recipients with vs without diabetes were older (53 vs 45 years; P <0.001) and more likely to be non‐white (41.0% vs 26.4%; P =0.001). Kidney allograft recipients with vs without diabetes had a higher risk of cellular rejection (19.7% vs 12.4%; P =0.024), but not of antibody‐mediated rejection (3.4% vs 3.7%; P =0.564). Graft function and risk of death‐censored graft loss were similar in the two groups, but kidney allograft recipients with diabetes had a higher risk of death and overall graft loss than those without diabetes. In a Cox regression model of non‐modifiable risk factors at time of transplantation, diabetes was found to be an independent risk factor for cellular rejection (hazard ratio 1.445, 95% CI 1.023–1.945; P =0.042). Conclusions: Kidney allograft recipients with diabetes at transplantation should be counselled regarding their increased risk of cellular rejection but reassured regarding the lack of any adverse impact on short‐to‐medium term allograft function or survival. What's new?: Diabetes remains the leading underlying cause of end‐stage kidney failure requiring kidney transplantation in developed countries. Rejection of the kidney allograft is the most feared complication after kidney transplantation from a patient perspective, but it is unclear if patients with diabetes have an increased risk of this complication. In this study, in the context of contemporary immunosuppression, we show that people with diabetes have an elevated risk of cellular rejection after kidney transplantation, but that this does not translate into adverse short‐to‐medium term kidney allograft outcomes. Our data allow targeted risk counselling for people with diabetes who are awaiting kidney transplantation.